Dual-imaging nanoparticles based on surface-modified magnetic nanoparticles and biodegradable photoluminescent polymers - Pandey, Nikhil; Iyer, Priyanka; Kadapure, Tejaswi D.; Yang, Jian; Nguyen, Kytai T.; Wadajkar, Aniket S. (Frontiers in Bioengineering and Biotechnology, 2025)
Theranostic nanoparticles, which combine diagnostic and therapeutic capabilities, have gained significant interest in disease management. We previously developed dual-imaging enabled cancer-targeting nanoparticles (DICT-NPs) composed of a biodegradable photoluminescent polymer (BPLP) and iron oxide-based superparamagnetic nanoparticles (MNPs). While DICT-NPs demonstrated cytocompatibility, magnetic targeting, and imaging capabilities, their fluorescence was inconsistent due to quenching by the MNP core and inefficient BPLP grafting. To address these limitations, we modified the MNP surface with silane, hydroxyapatite, or silane-coupled azide coatings before conjugating with BPLP. The resulting surface-modified DICT-NPs (mDICT-NPs) ranged in size from 200–350 nm and were cyto-compatible with human dermal fibroblasts and normal human prostate epithelial cells. Surface modifications and BPLP conjugation did not affect the superparamagnetic properties of the nanoparticles but enhanced fluorescence by ∼50% compared to the original DICT-NPs. Hydroxyapatite-modified DICT-NPs exhibited significant improvements, including sustained drug release of Paclitaxel and Docetaxel (71% and 68%, respectively, over 21 days), dose-dependent tumor cell uptake in melanoma, thyroid, and prostate cancer cells (with the highest uptake exceeding 60% at 500 μg/mL), and a reduction in cancer cell viability (less than 50% viability in TT thyroid cancer and KAT-4 cancer cell lines). These advancements represent a significant step in overcoming the fluorescence quenching issues associated with iron oxide-based magneto-fluorescent theranostic nanoparticle platforms, enhancing both their imaging and therapeutic potential in cancer treatment.